Parallel multigrid on locally refined meshes - Becker, Roland; Braack, Malte; Richter, Thomas (Reactive flows, diffusion and transport, 2007)
The use of PC-clusters gives the opportunity to solve three-dimensional flow problems to high accuracy at reasonable costs. The use of adaptive mesh refinement can increase the efficiency of such computations even more. However, the combination of multigrid, local mesh refinement and parallelization is not trivial. Therefore, this work addresses the following two topics in order to develope a tool for the simulation of complex flows: (i) multigrid algorithms on locally refined meshes, and (ii) the extension of multigrid to be used on parallel machines.